PERAN KEPEMIMPINAN KEPALA MADRASAH DALAM MENGEMBANGKAN BUDAYA MADRASAH - Mulyadi, Mulyadi (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2009)
The leadership of madrasa plays an important role in improving strong madrasa culture since such culture is influenced by how far the leadership of madrasa guides this school activities, both tangible and intangible guiding to establish strong madrasa culture. The strong madrasa culture can be established by four dimensions, namely commitment, capability, cohesion, and consistency. The role of such leadership in improving strong madrasa culture is a series of precess from the entirely madrasa organizational systems.The leadership role of madrasa in developing madrasa culture are to articulate the madrasa vision an mission, the values an belief within madrasa organizational, to create the madrasa symbol which is able to strengthen the unique of madrasa school organizational, to establish such reward system based on the norm and value of madrasa, to build the social and emotional relationship among teacher, student, and society based on the commitment and its mission and to design the structural of madrasaKeywords: leadership, developing, madrasa culture